ANALISIS BUDAYA LITERASI DALAM PEMBELAJARAN ANTOLOGI KOMIK SISWA SEKOLAH DASAR - Putri Wulandari Ningsih; Ira Nurmasari; Ahmad Mahmudi (PROCEEDING UMSURABAYA, 2022)
Reading is a basic skill that every child of the nation must have. Because a high literacy culture is proportional to the nation's ability to win global competition, especially in mastering science and technology, as well as labor market competition. The government really hopes for an increase in literacy culture in our country. This hope was continued by launching a movement for the growth o reading-writing culture, entitled â€œSchool Literacy Movementâ€. This movement is supported by researchers by trying to explore and create a fun literacy culture so that it attracts students to carry out literacy movements through comic anthology learning activities. The research method used in this study is a qualitative research method. This research was carried out at SD Muhammadiyah 16 Surabaya for fifth grade students consisting of 133 students divided into 8 classes. The sampling technique in this study is using a non-probability sampling technique. This study uses data collection techniques through observation, interviews and documentation. After observing, the researcher continued the process of collecting data through interviews with students, class teachers and also the principal. This series of research has been carried out and the results are obtained with the conclusion that literacy activities in making comics are very attractive to fifth grade students. The data collection shows that 88% of fifth grade students have been able to create interesting story ideas, 60% of fifth grade students still need guidance for mastery. sentences in illustrating pictures, and 69% of fifth grade students still need guidance to create a story line that is interconnected between one picture and another. The ability of students to create an image illustration can mostly narrate the intent and storyline of the image. The relationship of one picture with the next picture with a narrative shows the ability of students to create an idea.Â Keywords: Literacy culture; comic anthology; anime.Â